Expanding the scope of sulfinimine chemistry - Dutton, Justine (2017)
The synthesis and application of aldimines has been well documented in the last twenty years since Ellman’s publication of the synthesis of optically pure tert-butyl sulfinamide. Within the Stockman group their application to the aza-Darzens reaction has been explored. This work is an expansion of the previously reported aza-Darzens synthesis of aziridine 2-carboxylates with particular emphasis on increasing the scope and specific attention on heteroaryl-substituted aldimines and ketimines. A wide range of sulfinimines was screened with a variety of ester partners giving di- and tri-substituted aziridine 2-carboxylates. Overall the yields were good with di-substituted aziridines giving the best results. Tri-substituted aziridines were produced in variable yields and selectivity with some heteroaromatic substrates tolerated. Attempts to synthesise vinyl aziridine 2-carboxylates proved to be disappointing with a cyclopropane byproduct being observed. Attempts to avoid production of the byproduct were unsuccessful. It has been shown that vinyl aziridine 2-carboxylates will undergo rearrangement to cyclic sulfoximines. Mechanistic studies have indicated that this proceeds through a concerted sigmatropic rearrangement as neither radical traps nor polar solvents inhibited the reaction. The synthetic utility of aldimines as chiral precursors to isothiazolidines was briefly investigated, however this ultimately proved unsuccessful.